NURSING EDUCATORS’ PERCEPTIONS OF THE DOMAINS OF THE CORE COMPETENCIES FRAMEWORK FOR HEALTH PROMOTION - Ítala Keane Rodrigues Dias; Olga Feitosa Braga Teixeira; Ilara Parente Pinheiro Teodoro; Evanira Rodrigues Maia; Maria do Socorro Vieira Lopes; Maria de Fátima Antero Sousa Machado (Cogitare Enfermagem, 2018)
Objective: toinvestigate the perceptions of nursing professors from an undergraduate course of the domains of the Core Competencies Framework for Health Promotion and find out how these domains are applied in their teaching practice. Method: The study was conducted in 2017 at a public institution of higher education in the Northeastern Region of Brazil. Sixty-two (62) teachers who met the established inclusion and exclusion criteria were invited. Of these, 15 participated in the study. Results: The following categories emerged: “Nursing educators’ knowledge about health promotion: recognizing the domains” and “Nurse Educators’’ Practices in Health Promotion: Application of the domains of the Core Competencies Framework for Health Promotion.” Conclusion: Training and continuing education strategies on the referred subject should be provided.